Qualidade da linhaça marrom e dourada ozonizadas e armazenadas em embalagens - Bechlin, Taise Raquel (2019)
Flax (Linum usitatissimum L.) is rich in substances with functional properties. However, the conservation of these properties depends on good post-harvest practices and adequate sanitation and storage methods. The objective of this work was to evaluate the application of ozone in brown and golden flaxseed grown in different types of packaging and storage time and its possible influences on the quality of the oil, under the levels of water content, fungi count, determination of lipids, free fatty acids, peroxide index and color parameters. For this, a completely randomized experimental design was used, in a 3x2 factorial scheme, 3 types of packages, E1 (paper bags lined internally with polyethylene) and E2 (polypropylene plastic) packaging and control (C) and storage time , before and after (0 and 90 days) storage, with five replicates of 1.5 kg each. The effects of the treatment conditions were evaluated using analysis of variance, followed by Tukey's test, significant values were reported at the α = 0.05 level. According to the results obtained the ozonation in different types of packaging did not influence the results of the parameters water content and peroxide index before and after storage in brown and gold flaxseed. The variety of golden flaxseed showed a rise in free fatty acids after storage, as well as mean values of fungi counts higher than those of brown flaxseed, indicating higher contamination, however, these average values found for both varieties are in agreement with the considered levels safe for consumption. The lipid content was influenced by the packing factor for both varieties of linseed, and for brown flaxseed the packaging of paper bags coated internally with polyethylene presented better conservation maintaining the values after storage. As for gilded linseed, no significant differences were observed in the lipid values after storage in any of the packages, the fatty acid index was influenced only by storage. The color parameters were influenced by the type of packaging before the storage, that is, soon after the ozonation, and the packaging E1 presented values similar to the control indicating that the grains were not altered due to exposure to the ozone gas. In this way it can be affirmed that the packaging of paper bags lined internally with polyethylene presented better conservation of lipids and maintenance of color parameters, which is the most recommended for the storage of brown flaxseed. For gold flaxseed, further studies are needed to determine the best packaging for ozonation and storage.